Do your eyes give you away?: A validation study of eye-movement measures used as indicators for mindless reading - Steindorf, Lena; Rummel, Jan (Behavior research methods, 2020)
Identifying eye-movement measures as objective indicators of mind wandering seems to be a work in progress. We reviewed research comparing eye movements during self-categorized episodes of normal versus mindless reading and found little consensus regarding the specific measures that are sensitive to attentional decoupling during mind wandering. To address this issue of inconsistency, we conducted a new, high-powered eye-tracking experiment and considered all previously identified mind-wandering indicators. In our experiment, only three measures (reading time, fixation count, and first-fixation duration) positively predicted self-categorized mindless reading. Aside from these single measures, the word-frequency effect was found to be generally less pronounced during mindless-reading than during normal-reading episodes. To additionally test for convergent validity between the objective and subjective mind-wandering measures, we utilized eye-movement measures as well as thought reports, to examine the effect of metacognitive awareness on mind-wandering behavior. We expected that participants anticipating a difficult comprehension test would mind wander less during reading than would those anticipating an easy test. Although we were able to induce metacognitive expectancies about task difficulty, we found no evidence that these difficulty expectancies affected either subjectively reported or objectively measured mind wandering.
Published online: 27 February 2019
Gesehen am 24.03.2020